Incorporation of Sugarcane Bagasse Fiber on Concrete and Its Effect on Physical and Mechanical Properties - Nazario-Naveda, Renny (2025)
In the following investigation, concrete specimens incorporated with sugarcane bagasse fibers (SCBF) were manufactured to analyze their effects on their physical and mechanical properties. The fibers were collected from the waste generated by the sugar factories in the La Libertad region, Peru. SCBF were incorporated in different concentrations (0.5, 1, 1.5 and 2%) in the concrete mixing process. The effect of the incorporation of SCBF on the density and water absorption of the manufactured specimens were evaluated, also morphological variations were analyzed by Scanning Electron Microscopy (SEM). Likewise, the specimens were subjected to compression tests to verify their resistance. A good integration of the fibers in the concrete matrix was observed, the incorporation of SCBF produces a reduction in the number and size of pores. In addition, the increase in SCBF lightens the concrete, increasing the water absorption capacity. Mechanical tests show that the compressive strength increases with the incorporation of SCBF, reaching a maximum value using 0.5% fiber after 28 days of curing.